ROLE OF TEMPOROPARIETAL JUNCTION IN SELF-PERCEPTION - Seema Suman (International Journal of Multidisciplinary Research and Studies, 2021)
The ability to discern between representations of oneself and those of other people, as well as the ability to move between these representations, is a fundamental component of social cognition. Citation needed for example, if you are trying to see things from the perspective of another person, you have to switch back and forth between representing yourself as "self" and representing yourself as "other" in order to minimize the representation of your own perspective and maximize the representation of the other person's perspective. This is necessary in order to achieve the goal of seeing things from the perspective of the other person. In a similar vein, in order for a person to finish activities involving theory of mind, they must not represent their own beliefs, objectives, or intentions, but rather the beliefs, desires, and aims of another individual. When trying to empathize with another person, it is important to make a distinction between one's own affective state and the affective state that results from one's representation of the emotions of the other person. This is because one's own emotions can be influenced by one's interpretation of the other person's feelings (Singer and Lamm 2009). Again, this calls on the ability to move between representations of one's own emotions and those of other people.